Kemampuan Media Filter Manganese Greensand Dan Karbon Aktif Tempurung Kelapa Dalam Menurunkan Kadar Mangan (Mn) Pada Air Tanah, Kelurahan Gunung Kebayoran Baru Jakarta - Rojali, Rojali; Miftahul El-Jannah, Syarifah; Wartiniyati, Wartiniyati; Pangestu, Pangestu; Aliza , Fathiani Nur (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
Water is a vital resource and an essential human need for nearly all activities. Environmental Health Quality Standards for water encompass physical, biological, and chemical parameters, with a particular focus on Manganese (Mn) levels, which can be neurotoxic when consumed in excess. Filtration using a combination of Manganese Greensand and Coconut Shell Activated Carbon has been shown to effectively reduce Manganese levels in groundwater, achieving reductions of up to 80%. This study aims to evaluate the effectiveness of these media in lowering Manganese levels based on the volume of water filtered in RT 08, RW 01, Gunung Kebayoran Baru Subdistrict, South Jakarta. Utilizing a one-group pretest-posttest design, the study filtered groundwater with a Manganese concentration of 5 mg/L in volumes of 56, 112, 168, and 224 litres. The results indicated a decrease in Manganese levels, but the reductions did not meet the quality standards. The highest reduction percentage occurred at a volume of 56 litres, with a 48% decrease. Statistical analysis revealed a significant difference among the variations in water volume (p-value = 0.00001).  Keywords: Activated Carbon, Manganese Greensand, Environmental Health